How to bridge the nurse innovation–diffusion gap? An in-depth case study of Create4Care - Rigtering, Coen; Spaans, Lara J.; de Jong, Jeroen P. J. (Frontiers in Public Health, 2023)
Nurses frequently innovate in response to operational failures, regulations, procedures, and/or other workflow barriers that prevent them from delivering high-quality patient care. Unfortunately, most nurse innovations do not diffuse to a broader audience, depriving other nurses of from taking advantage of solutions that have already been developed elsewhere. We develop a qualitative case study of a medical makerspace that reports unusually high rates of nurse innovation diffusion. Our data collection includes on-site observations, archival data, secondary data, and fifteen in-depth interviews with key informants. The data shows that personal, organizational, regulatory, and market barriers prevent nurses from further developing and diffusion their innovations in an anticipatory manner. That is, because nurses expect that transforming an initial solution into an innovation that can be shared with others will be too time-consuming and difficult they do not proceed with further development. The medical makerspace that we investigated adequately addresses this lack-ofdiffusion problem by developing an innovation ecosystem that largely takes over the innovation and diffusion process.